Reputational and cooperative benefits of third-party compensation - Dhaliwal, Nathan A.; Patil, Indrajeet; Cushman, Fiery (Organizational behavior and human decision processes, 2021)
•Third-party compensators are perceived as superior cooperation partners.•Even punitive observers prefer compensators as cooperation partners.•Third-party compensating is an honest signal of lower Dark Triad traits.•We examine these topics across 24 studies, N > 21,000. Although third-party punishment helps sustain group cooperation, might victim compensation provide third parties with superior reputational benefits? Across 24 studies (N = 21,296), we provide a comprehensive examination of the consequences of the choice between punishment and compensation. What do people infer from, and how do they respond to, the choice of punishment versus compensation? Across various contexts ranging from economic games, to workplace injustice, to people’s own personal experience of witnessing third-party responses in their daily lives, we find that compensating victims leads to greater reputational and partner choice benefits relative to punishing perpetrators. In fact, even people who themselves prefer to punish still prefer social partners who compensate. We also find that the signal that is sent via third-party compensating is an honest signal—people who choose to compensate rather than punish score lower on measures of trait Machiavellianism, narcissism, and psychopathy. Furthermore, we find that the personal decision of whether to compensate or punish is influenced by both injunctive and descriptive norms. These findings provide an extensive analysis of the causes and consequences of third-party responding to moral violations.